2016
DOI: 10.2147/ott.s115892
|View full text |Cite
|
Sign up to set email alerts
|

Atypical aleukemic presentation of large granular lymphocytic leukemia: a case report

Abstract: Large granular lymphocytic leukemia (LGLL) is a rare lymphoproliferative disorder of transformed natural killer or T-cells attributed to chronic exposure to the proinflammatory cytokine IL-15. Diagnosis of the majority of T-cell LGLL is established by documenting clonal large granular lymphocytes (LGLs) in peripheral blood, by morphology and immunophenotype. The proteasome inhibitor bortezomib is known to target molecular pathways downstream of the IL-15 receptor signaling and has been proposed as a therapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, it has also been shown that loss of Tet2 associated either with Dnmt3a or Tet1 in double KO mice can result in lymphoid malignancies with a phenotype similar to CLL B cells [ 2 , 14 ]. In humans, our previous work sustains an important concomitant impact of TET1 , TET2 and DNMT3A aberrant expression in CLL patients with aggressive diseases, as they are the epigenetic regulators with the lowest expression in CLL patients with a global deficit in cytosine derivatives including 5-mCyt and 5-hmCyt and the worst prognosis [ 15 , 16 ]. Moreover, in CLL patients, higher levels of DNMT3A and TET1 were associated with longer treatment-free survival, thus supporting their function as tumor suppressors.…”
mentioning
confidence: 75%
“…However, it has also been shown that loss of Tet2 associated either with Dnmt3a or Tet1 in double KO mice can result in lymphoid malignancies with a phenotype similar to CLL B cells [ 2 , 14 ]. In humans, our previous work sustains an important concomitant impact of TET1 , TET2 and DNMT3A aberrant expression in CLL patients with aggressive diseases, as they are the epigenetic regulators with the lowest expression in CLL patients with a global deficit in cytosine derivatives including 5-mCyt and 5-hmCyt and the worst prognosis [ 15 , 16 ]. Moreover, in CLL patients, higher levels of DNMT3A and TET1 were associated with longer treatment-free survival, thus supporting their function as tumor suppressors.…”
mentioning
confidence: 75%
“…Large granular lymphocytic (LGL) leukemia is a type of chronic leukemia comprising 2–5 percent of chronic lymphoproliferative diseases and has a median age of diagnosis of about 66.5 years [ 1 ]. The World Health Organization (WHO) classifies LGL disorders into three types as follows: T cell large granular lymphocytic leukemia (T-LGLL), which is the most common type, chronic lymphoproliferative disorders of NK cells (CLPD-NK) comprising about 5% of LGL leukemia, and aggressive NK cell leukemia accounting for about 10% of LGL leukemia [ 1 , 2 ]. LGL cells are composed of CD3-NK cells and CD3+ T cells that are programmed to bind to infected target cells and undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of LGL leukemia requires a peripheral smear and bone marrow biopsy examination and flow cytometry to determine T cell versus NK cell lineage. A circulating LGL count of >0.4 or 0.5 g/L is also required for diagnosis [ 1 ]. Other causes, such as viral infections, hairy cell leukemia, autoimmune neutropenia, and myelodysplastic syndrome, must be ruled out [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Up to one third of cases with T-LGL have been shown to have coexistent RA, compared with the frequency of RA in the general population, which is 0.5% to 1%. 4 , 5 T-LGL is usually diagnosed in the 50s and 60s and involves males and females equally. 1 Felty’s syndrome (FS) is defined by the triad of variable splenomegaly, low neutrophil count, and destructive arthritis and is usually seen in <1% of patients with RA.…”
Section: Introductionmentioning
confidence: 99%